BADUY PLURALISM: FROM MYTH TO REALITY - Abdurrahman Misno Bambang Prawiro (Graduate Program of Pontianak Institute of Islamic Studies, 2013)
Indonesia is a land of many tribes, with each tribe having different customs. However they have a bond in the form of the state motto, Bhineka Tunggal Ika. This motto is based on a philosophy embraced by every tribe in the form of the teachings passed down from the ancestors such as pantun (Malay poetic form), rhyme, guguritan (Sundanese literary works), history and myths. Myths here are stories about things that happened in the past in the form of the history of the origins of man and nature, or the origin of a nation. Myths as a local wisdom are believed to be the truth by every member of the tribe applied in everyday life. This includes the myth that tells about human cultural diversity (plurality), and the community will implement its content. What about the Baduy community in Banten, do they have myths and apply the myths that deal with pluralism in their life? The Baduy are one of the ethnic groups in Indonesia who have myths about the creation of the universe, human origins, and even myths about the events that will occur. The myth about the origin of humans in the Baduy community begins with the creation of Adam as the first human, and then he had children that gave birth to the whole nation in the world. Because every human in the world is the great-grandsons of Adam, the Baduy believe that all humanity is dulur (brother) despite differences in customs and religion. The reality of social life of the Baduy community, either Baduy Dalam (inner baduy) or Baduy Luar (outer baduy) is that they greatly respect all mankind despite the different cultures and religions. Prohibition to enter the Baduy traditional village for foreigners is because of historical factors, namely the agreement made by their ancestors with the Dutch. This research concluded that the Baduy society is a society that understands the plurality of cultures; it is based on a myth that they believe and apply in their life about tolerance of other religions. Key Word: Pluralism, Baduy, Lebak Banten, myth and reality